PENERAPAN LESSON STUDY SEBAGAI UPAYA PENINGKATAN KOMPETENSI TUTOR KEAKSARAAN FUNGSIONAL - Putu Ashintya Widhiartha; Dwi Sudarmanto (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2009)
Lesson study is an approach in improving the teacher’s competence through colaborative and continuous analysis of the instruction based on collegial and mutual learning principles. This approach includes teacher’s participation to be active in small discussion group. This research was conducted to develop lesson study approach to improve the competence of functional literacy tutors. Viewed from the methodology employed, the research which was conducted in Sukolilo Sub-District, Surabaya, is classified as an action research. To meet the objectives, the research was undertaken in four cycles as from November 2007 through February 2008. The results show there is a significant improvement of the functional literacy tutors’ competence.Based on the experience in conducting this action research, some recommendations are given in the application of lesson study model.